Litigators’ Lack of Knowledge and Legal Ethics: An Analysis of Judges’ Narratives in Cases of Violence Against Women and Family Group Members - Del Mastro Puccio, Fernando (2025)
In this article, we explore how a group of judges describe their experiences with the lack of knowledge displayed by lawyers who litigate before their courts. Through narrative interviews with five judges from the module of the National Specialized Justice System for the Protection and Punishment of Violence against Women and Members of the Family Group (SNEJ), we find that litigators are portrayed as professionals who do not do their homework, fail to prepare, lack even the minimum knowledge required before entering a hearing, and normalize their own ignorance. In response to these situations, judges present themselves as figures of authority who seek to preserve the integrity of hearings by giving lawyers a few minutes to read the case file, guiding them so they can fulfill their role, reprimanding or firmly exhorting them, or even urging defendants to change lawyers, among other measures. By contrast, judges do not impose fines or formal sanctions, rarely invoke ineffective assistance of counsel, and do not report cases to bar associations. On several occasions, judges express doubts about the role they should play when confronted with litigators’ lack of knowledge. At the same time, for most judges, ignorance is problematic but does not properly constitute an ethical issue, since it does not involve an intention to deceive or cause harm, nor does it rise to problems such as corruption. In many cases, there does not appear to be a clear conception of what constitutes a violation of professional ethics in litigation.